An Enhanced Pathfinder Algorithm based MCSA for rotor breakage detection of induction motor - Halder, Sudip; Dora, Bimal Kumar; Bhat, Sunil (Journal of computational science, 2022)
This paper proposes a new broken rotor bar (BRB) finding technique based on a novel hybrid algorithm, namely the Enhanced Pathfinder Algorithm (EPFA). Compared to existing optimization algorithms, this proposed approach provides more balanced exploration and exploitation. The main task regarding rotor fault detection is to identify sideband frequency components (SFCs) corresponding to the fault and in this context proposed method overcomes the disadvantages of traditional frequency domain analysis, such as short data length, effects of spectral leakage, and insufficient sampling frequency. To achieve the proposed diagnosis approach, a signal model for faulty current and a function of residual error are used for the formulation of a nonlinear least-square problem. The method is first tested on a synthetic fault signal, and finally, to validate the proposed technique, a Finite Element Model (FEM) of the induction motor is simulated in the ANSYS 2D workbench. •Enhanced Path Finder Algorithm (EPFA).•FEM model of the machine to be diagnosed.•Early stage Broken Rotor Bar detection.•Assessment of fault severity.